Basic movement skills profile for early childhood motor development - Sukmawati, Noviria; Melianty, Selvi; Almigo, Nuzsep; Wati, Komang Julia; Azhari, Robbani Azzahra (Physical Education Departement of University PGRI Jombang, 2025)
This study aims to determine the profile of basic motion skills and motor development of early childhood aged 4-6 years. This study will focus on collecting data related to basic early childhood movement skills, taking into account various aspects that affect motor development. Research using descriptive quantitative methods. The population in this study were children who were at the age of 4-6 years in kindergarten (TK) in the city of Palembang. The sample used a random sampling technique with a total of 60 children. Collection using tests, observations, and interviews. The research instrument used the Test of Gross Motor Development-2. Data analysis uses quantitative analysis and descriptive analysis. The results showed that TK Negeri 4 Pembina had the highest average score in the category of very good 31.25% and good 37.92%, showing good motor skills in the majority of children. TK Harapan Bangsa 3 recorded the highest score in The Good category of 45.42% but low in the very good category of 25.83%. TK Gita Wijaya has the highest score in the category of enough 25.00% and less than 5.00%, indicating the need for more attention to the development of children's motor skills. Research in three kindergartens in Palembang shows the majority of children have good motor skills, especially in skills such as balanced walking and sprinting.Further research suggestions could be to put together structured exercise programs and training for educators to optimally improve children's motor skills.